Synthesis and magnetic properties of bundled and dispersed Co3O4 nanowires. (March 2016) - Zhang, B.B.; Wang, P.F.; Xu, J.C.; Han, Y.B.; Jin, H.X.; Jin, D.F.; Peng, X.L.; Hong, B.; Li, J.; Yang, Y.T.; Gong, J.; Ge, H.L.; et al.
Graphical abstract: Highlights: Co3 O4 nanowires possessed the same diameter and the different interwires distance. All samples possessed antiferromagnetism and superparamagnetism at high temperature. The exchange bias effect was observed at low temperature. The surface spin coupling restrained the surface effect of magnetic nanostructures. Abstract: The magnetic Co3 O4 nanowires were synthesized using the templates of SBA-15, and then the well-dispersed nanowires (D-wires) were separated from the bundled ordered nanowires (B-wires) with the centrifugal technique. TEM images indicated that D-wires were highly dispersed Co3 O4 nanowires and B-wires existed in bundles. All samples possessed the antiferromagnetism and superparamagnetism at high temperature. After revealing the intrinsic magnetic properties of Co3 O4 nanowires with D-wires, the magnetic behavior of B-wires was discussed in detail, and then the magnetic interaction between neighboring nanowires could be deduced. The exchange bias effect from the body Co3 O4 antiferromagnetism and surface ferromagnetism was observed at low temperature. The magnetization of B-wires was higher than that of D-wires, which was attributed to the constraint of the surface spin coupling between the neighboring nanowires to the surface affect of nanostructures.